Aerodynamic Investigation of Motorcycle Windshield Design at Different Height Configurations - Marzuki, Muhammad Arif; Abdul Ghafir, Muhammad Fahmi (Progress in Aerospace and Aviation Technology, 2026)
The objective of this study was to investigate how variations in motorcycle windshield height influence aerodynamic flow, drag coefficient, and rider comfort, and to determine the relationship between windshield height and drag coefficient. Three windshield height configurations were examined using computational fluid dynamics (CFD) simulations in Ansys Fluent, with geometry modeled in SolidWorks 2023: Model 1 (205 mm), Model 2 (250 mm), and Model 3 (330 mm). Simulations were conducted at operating speeds of 110, 140, and 160 km/h. Variations in drag coefficient with velocity were assessed, and static pressure fields on the rider were also evaluated. The results show that lower windshields produce less aerodynamic drag, with Model 1 yielding the lowest drag coefficient. Pressure-contour analysis further indicates that taller windshields reduce the overall pressure experienced by the rider. These findings demonstrate the significant role of windshield height in motorcycle aerodynamics and rider comfort and may support riders and manufacturers in optimizing motorcycle performance while improving the riding experience.